Practicable Thinnings (in Naturally Regenerated Young Crops of Teak) - Sagreiya, K. P. (Indian Forester, 1956)
The paper describes a feasible method of thinning irregular young crops of teak, of coppice, seedling-coppice and seedling origin, with the help of intelligent Forest Guards and mazdoors. It prescribes selection of the best stems and then giving each of them the optimum growing space, according to the formula D = 1.5 (d+4) where D is the diameter of the growing space in feet, and d is the diameter of the stem in inches. Accordingly, two adjacent stems of diameters d1 and d2 inches are considered as ideally spaced when the distance between them is equal to 1.5 {d1 + d2/2 +4}feet. To check that thinnings to the desired intensity have been carried out, it is suggested that small plots be laid out and the arithmetical average diameter of /lites determined and checked against the approximate formula- N = ( 150/X + 4)2 where N is the number of stems per acre. It is emphasized that due allowance should be made for vacant spaces which are likely to be left wherever the original crops is not fully stocked.